2019
DOI: 10.1007/s00441-019-03038-2
|View full text |Cite
|
Sign up to set email alerts
|

The digestive system of xenacoelomorphs

Abstract: Interest in the study of Xenacoelomorpha has recently been revived due to realization of its key phylogenetic position as the putative sister group of the remaining Bilateria. Phylogenomic studies have attracted the attention of researchers interested in the evolution of animals and the origin of novelties. However, it is clear that a proper understanding of novelties can only be gained in the context of thorough descriptions of the anatomy of the different members of this phylum. A considerable literature, ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Fig. 1), consistent with the presence of a syncytial digestive system, which has been reported for some acoels (Smith, 1981;Gavilán et al, 2019). Shortly after hatching, we sorted G0 animals based on the presence of transgene expression and the intensity of fluorescence: only those exhibiting strong fluorescence and the largest area of expression were raised to adulthood and screened regularly for continued transgene expression.…”
Section: Establishment Of Stable Transgenic Linessupporting
confidence: 78%
“…Fig. 1), consistent with the presence of a syncytial digestive system, which has been reported for some acoels (Smith, 1981;Gavilán et al, 2019). Shortly after hatching, we sorted G0 animals based on the presence of transgene expression and the intensity of fluorescence: only those exhibiting strong fluorescence and the largest area of expression were raised to adulthood and screened regularly for continued transgene expression.…”
Section: Establishment Of Stable Transgenic Linessupporting
confidence: 78%
“…The phylum Xenacoelomorpha comprises an assemblage of marine worms that have a simple body plan without a throughgut (Hejnol and Pang, 2016;Telford and Copley, 2016;Gavilán et al, 2019). They are of particular interest for evolutionary studies because of controversy regarding their phylogenetic position in the animal kingdom.…”
Section: Luqin-type Neuropeptide Signaling In Xenacoelomorphs: Receptmentioning
confidence: 99%
“…Molecular-genetic studies have revealed important themes in gut development, and several reviews of the special issue summarize the current knowledge in this area [Annunziata et al 2019 Contrasting with a strongly conserved repertoire of genetic mechanisms acting in gut development is the evident diversity of the architectures and cellular compositions of the digestive systems, which results from the need to adapt to the different types of food that animals consume. Examples of gut diversity surveyed in detail in this special issue include the sponges (Godefroy et al 2019), acoels (Gavilán et al 2019) and molluscs (Lobo-da-Cunha 2019).…”
Section: Conserved Genetic Mechanism Specify Diverse Gutsmentioning
confidence: 99%